Potensi Tulang Ikan Nila (Oreochromis Niloticus) untuk Memenuhi Kecukupan Kalsium: The Potential of Tilapia Bone (Oreochromis Nilotikus) to Meet Calcium Sufficiency - Tarigan, Novriani; Sihotang, Urbanus (Amerta Nutrition, 2024)
Background: Calcium is an essential nutrient that plays a role in the human biological system, especially bones. The study results in Benin showed that the calcium intake of pregnant women was low, and Kinshella reported that the calcium intake of low-income pregnant women was very low. In Indonesia, the calcium intake of pregnant women is 403.5±343.1 mg/day from 1200 mg/day. The source of calcium is milk and its processed products. Objectives: This study aims to obtain fishbones rich in calcium from fish processing waste. Fishbones can be an alternative source of calcium other than milk and are cheaper. Methods: This study was conducted using two laboratory experiment methods. The fishbone sample is a fish skeleton that is fish processing waste. The first method was to press the fishbones for 2 hours and dry them in a cabinet dryer for 20 hours at 60°C. In the second method, the fishbones were soaked using as much as 30 ml per kg of vinegar acid for 10 minutes. Next, it was dried in a cabinet dryer for 4 hours at 60°C. These two methods tested the levels of proximate and calcium in fishbone meal. Results: The moisture content of the two flours was almost the same, the protein, fat, and calorie content was higher in the first experimental fishbone meal. The second trial of fishbone meal has a higher ash and carbohydrate content. Meanwhile, the calcium level of the fishbone meal in the second trial was four times that of the first. Conclusions: To achieve daily calcium sufficiency, one should consume 10 g of calcium flour. Further research is needed to determine calcium absorption in the body and the development of consumption in food applications.